The problem of the uninsured - Isaac Ehrlich; Yong Yin (Institute for the Study of Labor (IZA), 2012)
The problem of the uninsured - those eschewing the purchase of health insurance policies - cannot be fully understood without considering informal alternatives to market insurance called self-insurance and self-protection, including the publicly and charitably-financed safety-net health care system. This paper tackles the problem of the uninsured by formulating a full-insurance paradigm that includes all 4 measures of insurance as interacting components, and analyzing their interdependencies. We apply both a baseline and extended versions of the model through calibrated simulations to estimate the degree to which these non-market alternatives can account for the fraction of the non-elderly adults who are uninsured, and estimate their behavioral and policy ramifications. Our results indicate that policy analyses that do not consider the role of self-efforts to avoid health losses can grossly distort the success of the ACA mandate to insure the uninsured and to improve the health and welfare outcomes of the previously uninsured.
Keywords: G22; H42; I13; I28; 330; health insurance; health care; uninsured; self-insurance; self-protection; Krankenversicherung; Gesundheitswesen; Selbstversicherung; Wohltätigkeit; USA